Activity demands during multi-directional team sports: A systematic review - Taylor, J. B.; Wright, A. A.; Dischiavi, S. L.; Townsend, A.; Marmon, A. R. (Sports Medicine, 2017)
Background: Late-stage rehabilitation programs often incorporate `sport-specific` demands, but may not optimally simulate the in-game volume or intensity of such activities as sprinting, cutting, jumping, and lateral movement. Objective: The aim of this review was to characterize, quantify, and compare straight-line running and multi-directional demands during sport competition. Data Sources: A systematic review of PubMed, CINAHL, SPORTDiscus, and Cochrane Central Register of Controlled Trials databases was conducted. Study Eligibility Criteria: Studies that reported time-motion analysis data on straight-line running, accelerations/decelerations, activity changes, jumping, cutting, or lateral movement over the course of an entire competition in a multi-directional sport (soccer, basketball, lacrosse, handball, field hockey, futsal, volleyball) were included. Study Appraisal and Synthesis Methods: Data was organized based on sport, age level, and sex and descriptive statistics of the frequency, intensity, time, and volume of the characteristics of running and multi-directional demands were extracted from each study. Results: Eighty-one studies were included in the review (n = 47 soccer, n = 11 basketball, n = 9 handball, n = 7 field hockey, n = 3 futsal, n = 4 volleyball). Variability of sport demand data was found across sports, sexes, and age levels. Specifically, soccer and field hockey demanded the most volume of running, while basketball required the highest ratio of high-intensity running to sprinting. Athletes change activity between 500 and 3000 times over the course of a competition, or once every 2-4 s. Studies of soccer reported the most frequent cutting (up to 800 per game), while studies of basketball reported the highest frequency of lateral movement (up to 450 per game). Basketball (42-56 per game), handball (up to 90 per game), and volleyball (up to 35 per game) were found to require the most jumping. Limitations: These data may provide an incomplete view of an athlete`s straight-line running load, considering that only competition and not practice data was provided. Conclusions: Considerable variability exists in the demands of straight-line running and multi-directional demands across sports, competition levels, and sexes, indicating the need for sports medicine clinicians to design future rehabilitation programs with improved specificity (including the type of activity and dosage) to these demands.